The responsibility of the scientist: What can history teach us about how scientists should handle research that has the potential to create harm?. (13th August 2013) - Herrlich, Peter
Abstract : Do scientists bear the responsibility for how their research is used? What can we learn from wartime and more recent examples of how scientists have handled dual‐use problems of research?